Thermo-hydro-mechanical-chemical coupling effects on the integrated optimization of CO2-EOR and geological storage in a high water-cut reservoir in Xinjiang, China - Yifan Ma; Zongfa Li; Hui Zhao; Botao Liu; Fankun Meng; Chuixian Kong; Yiyang Yin; Haotian Zheng; Yi Wu; Chenjie Luo (Energy Geoscience)
Carbon dioxide-enhanced oil recovery (CO2-EOR) and storage is recognized as an economically feasible technique if used in suitable reservoirs. The type or form and capacity of this CO2 sequestration technique is synergistically affected by heat, flow, stress, and chemical reactions. Aimed at addressing the technological issues in applying CO2-EOR and storage in a high water-cut reservoir in Xinjiang, China, this paper proposes a thermo-hydro-mechanical-chemical coupling method during CO2 flooding. The potential of CO2 sequestration and EOR in the target reservoir is discussed in combination with the surrogate optimization method. This method works better as it considers the evolution of structural trapping, capillary trapping, solubility trapping, and mineral trapping during CO2 injection as well as the influence the physical field has on the sequestration capacity for different forms of CO2 sequestration. The main mechanisms of CO2 sequestration in the high water-cut reservoir is structural trapping, followed by capillary trapping. Solubility trapping and mineral trapping have less contribution to the total sequestration capacity of CO2. After optimization, the cumulative oil production was 2.36 × 106 m³, an increase of 0.25 × 106 m³ or 11.9 % compared to the pre-optimization value. The CO2 sequestration capacity after optimization was 1.39 × 106 t, which is an increase of 0.23 × 106 t compared to values obtained before optimization; this effectively increases the area affected by CO2 by 24.4 %. Of the four trapping mechanisms, capillary trapping and structural trapping showed a high increase of 32.5 % and 17.28 %, respectively, while solubility trapping and mineral trapping only led to an increase of 5.1 % and 0.43 %, respectively. This research could provide theoretical support for fully utilizing the potential of CO2-EOR and sequestration technology.